2017
DOI: 10.18632/oncotarget.16424
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory network of GATA3 in pediatric acute lymphoblastic leukemia

Abstract: GATA3 polymorphisms were reported to be significantly associated with susceptibility of pediatric B-lineage acute lymphoblastic leukemia (ALL), by impacting on GATA3 expression. We noticed that ALL-related GATA3 polymorphism located around in the tissue-specific enhancer, and significantly associated with GATA3 expression. Although the regulatory network of GATA3 has been well reported in T cells, the functional status of GATA3 is poorly understood in B-ALL. We thus conducted genome-wide gene expression associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…A series of GWASs and subsequent validations have revealed that SNPs in PIP4K2A locus are significantly associated with ALL susceptibility, possibly through impact on PIP4K2A expression, indicating the potential role of PIP4K2A over-expression in leukemogenesis. Therefore, 214 genes were identified to be associated with PIP4K2A expression with the similar pipeline we used previously (Hou et al, 2017). Although association strength varied in different types of leukemia, or even subtypes of B-ALLs, almost all of these candidates can be validated in B-ALL of another big patient cohort, while a large proportion of them can also be validated in other types of leukemia in terms of expression association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of GWASs and subsequent validations have revealed that SNPs in PIP4K2A locus are significantly associated with ALL susceptibility, possibly through impact on PIP4K2A expression, indicating the potential role of PIP4K2A over-expression in leukemogenesis. Therefore, 214 genes were identified to be associated with PIP4K2A expression with the similar pipeline we used previously (Hou et al, 2017). Although association strength varied in different types of leukemia, or even subtypes of B-ALLs, almost all of these candidates can be validated in B-ALL of another big patient cohort, while a large proportion of them can also be validated in other types of leukemia in terms of expression association.…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphisms around PIP4K2A are associated with ALL susceptibility through impacting expression level of PIP4K2A , and accumulating evidence indicates the potential role of PIP4K2A on cancer cells, however, it is poorly understood that how PIP4K2A impact on tumorigenesis (including leukemogenesis). In this study, we conducted array based genome-wide gene expression association analyses to investigate the potential regulatory network of PIP4K2A in leukemia, which is proved to be efficient in our previous work (Hou et al, 2017). Besides, we will also systematically examine the PIP4K2A status in multiple cancers and evaluate its prognostic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the actin-binding protein Ccdc88a , which plays a role in cytoskeletal remodeling and cell migration following activation of Akt downstream of EGFR ( 54 ) and can also enhance Akt signaling ( 42 , 55 ). Third, integral membrane protein 2A ( Itm2a ) is a type II integral membrane protein that has been associated with an enhanced GATA3-mediated regulatory network in B ALL ( 56 ). Chd3 encodes a chromatin remodeler with unexplored function in lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…To gain more insights into the mechanism of GATA3 mediated l ‐Asp resistance, we determined whether GATA3 can regulate the JAK‐STAT signaling pathway. 8 As shown in Figure 4E , GATA3 overexpression resulted in increased expression of CRLF2 and phosphorylation of JAK2 and STAT3. Intriguingly, inhibition of JAK2‐STAT3 signaling by ruxolitinib suppressed autophagy activation, which in turn sensitized B‐ALL cells to l ‐Asp treatment (Figure 4F,G ), indicating another layer of regulation of autophagy by GATA3 via posttranslation regulation of JAK2‐STAT3 signaling in B‐ALL cells.…”
mentioning
confidence: 79%